Hubungan Stigma Keluarga Dengan Penerimaan Keluarga Terhadap Orang Dengan Gangguan Jiwa Di Wilayah Kerja Puskesmas Ladang Tuha Kecamatan Pasie Raja Aceh Selatan - Sry Rizki; Asmima Yanti (STIKES Columbia Asia Medan, 2025)
Mental disorders are health problems that affect individuals, families, and communities, where the negative stigma given by families to members with mental disorders can influence the acceptance and support they receive. This study aimed to determine the relationship between family stigma and family acceptance toward people with mental disorders (PWMD) in the working area of Ladang Tuha Public Health Center, Pasie Raja Subdistrict, South Aceh. The research employed a descriptive-analytic design with a cross-sectional approach, involving 65 families selected using the total sampling technique. The instruments used were the Internalized Stigma of Mental Illness (ISMI) questionnaire and a family acceptance questionnaire, analyzed using the Chi-Square test with a significance level of 0.05. The results showed that the majority of respondents had low stigma (67.7%) and poor acceptance (61.5%), with a p-value = 0.000, indicating a significant relationship between family stigma and family acceptance toward PWMD. The study concluded that the lower the family stigma, the better the acceptance toward PWMD; thus, educational efforts and family empowerment are needed to reduce stigma and improve acceptance.